Pregnant women's perception of the importance of reducing mosquito infestation in hospitals: Evidence from Selangor, Malaysia - Mei, Li Ji; Shukor, Shureen Faris Abdul; Noor, Mohd Sallehuddin Bin Mat; Muthuveeran, Adam Aruldewan S (Asian Journal of Empirical Research, 2025)
Mosquito infestation poses a serious threat to Selangor, Malaysia. Pregnant women are exposed to the risk of mosquito-borne diseases during hospital visits. This study aimed to examine pregnant women's perceptions of the importance of reducing mosquito infestation and whether demographic characteristics influence their perceptions. A quantitative research design was used in this study. A questionnaire survey was conducted among 100 pregnant women attending a tertiary government hospital in Selangor, Malaysia. The questionnaire included demographic variables as well as a five-point Likert scale to measure the importance of reducing mosquito infestation. Descriptive statistics showed that participants considered reducing mosquito infestations in hospitals to be "very important." One-way ANOVA showed that there were no statistically significant differences in the importance scores of different demographic variables (p > 0.05), indicating that the cognition was relatively consistent among different subgroups. However, education level showed a near-significant effect, suggesting that the underlying trends warrant further exploration. These findings highlight the overall importance of reducing mosquito infestation in hospitals, underscoring the value of broad-based health education and public health interventions. Future studies with larger samples are recommended to explore potential subgroup differences.